Quantitative Characteristics of Brown Bear (Ursus arctos L.) Feeding on Umbelliferae Plants - S.S. Ogurtsov (Учёные записки Казанского университета: Серия Естественные науки)
The natural feeding preferences of brown bear for Umbelliferae plants have been considered. The general quantitative characteristics of feeding on forbs have been revealed for bears inhabiting the Central Forest State Nature Biosphere Reserve (Tver region). Umbelliferae plants dominate in the diet of brown bears during late spring and early summer. Angelica sylvestris, Chaerophyllum aromaticum, Aegopodium podagraria, and Heracleum sibiricum are most frequently consumed by bears in the nature reserve. Feeding on A. sylvestris is directly associated with the overall abundance of this plant species and varies depending on its phenological stages. The preference is given to widely distributed age-size forb groups with the thickest stems. The maximum share of consumed plants has been observed in small forest herblands and overgrown fields adjacent to the forest cover. In all the biotopes, bears are attracted to herb sites with the highest abundance of consumed plants. Ch. aromaticum and H. sibiricum are distributed more locally and, therefore, less common in the diet of bears.